The Effect of Trust, Perceived Risk, Perceived Benefit and Cost On Customer Online Purchase Intention (An Empirical Study At Accounting Students of Brawijaya University and Muhammadiyah University of Malang) - Lita Widya Rahayu (Fakultas Ekonomi dan Bisnis Universitas Brawijaya, 2015)
The use of internet and e-commerce in Indonesia grows continuously. The Internet has changed the consumer behaviour in meeting their needs. Therefore, this study aims to examine the factors affecting customer’s online purchase intention to use e-commerce. This research is conducted at Economic and Business faculty of Brawijaya University and the University of Muhammadiyah Malang using a survey method. The independent variables of this study are trust, perceived risk, perceived benefit and cost. Purchase intention to use e- commerce in online shopping is the dependent variable. Partial Least Square (PLS) is used to test the hypothesis in First Order Construct (FOC) with the samples of 340 respondents. The results of this model analysis show that trust, perceived risk, perceived benefit has a positive effect on customer’s online purchase intention to use e-commerce. However it is found that cost negatively affects costumer’s online purchase intention to use e-commerce. Therefore, customer’s online purchase intention will determine the customer decision to conduct transaction or not. The implications of the research are relevant for management and system developers toconsider intention, trust, perceived risk, perceived benefit in applying and developing e-commerce transaction.Keywords: Trust, Perceived Risks, Perceived Benefit, cost, e-commerce